IMPLEMENTASI PERATURAN KEPALA BADAN PERTANAHAN NASIONAL NOMOR 1 TAHUN 2010 TENTANG STANDAR PELAYANAN DAN PENGATURAN PERTANAHAN (Studi Kasus Pada Kementerian Agraria dan Tata Ruang Badan Pertanahan Nasional Kota Pekanbaru) - Suprenda, Astri; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The importance of land uses for the person or legal entity demands guarantees of legal certainty over land, particularly on the status of ownership of land rights relating to land of certificate will provide clarity about the person or legal entity becomes the holder of the rights over the land, nor the certainty about the layout, the broad restrictions, and so on. Therefore the national land Agency Pekanbaru is a government agency responsible for providing services in accordance national land Agency Chief Regulations of the Republic of Indonesia number 1 of 2010 on standard services and Land Arrangements. The purpose of this research is to know how the implementation of the national land Agency Chief Regulation number 1 of 2010 about the standard of service and land Arrangement and the factors that influence the national land Agency Chief Regulations of the Republic of Indonesia number 1 of 2010 on standard services and Land Arrangements.The concept of the theory that the author use is public policy, implementation of policy and public services. This research uses qualitative research methods with the study of descriptive data. In data collection, the author uses the techniques of observation, interview and the study of librarianship. With the use of key informants as a source of information and technique of triangulation as a source in the validity of the data.The results of this research show that the implementation of the national land Agency Chief Regulation number 1 of 2010 about the standard of service and Setting of land not yet running optimally. It can be seen from to benefits and have not yet any change after the enactment of the national land Agency Chief Regulation number 1 of 2010. The factors that inhibit the implementation of the national land Agency Chief Regulation number 1 of 2010 about the standard of service and setting the amount of the Land is the lack of adequate human resources di BPN the city of Pekanbaru, as well as the lack of good communication between agencies-agencies that deals in the management of the registration certificate of the land first.Keywords: implementation of policy, Service, Land Certificates and registration first.